Cola beverage consumption delays alveolar bone healing: a histometric study in rats - Juliana Mazzonetto Teófilo; Daniel Vilela Leonel; Teresa Lamano (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Epidemiological studies have suggested that cola beverage consumption may affect bone metabolism and increase bone fracture risk. Experimental evidence linking cola beverage consumption to deleterious effects on bone is lacking. Herein, we investigated whether cola beverage consumption from weaning to early puberty delays the rate of reparative bone formation inside the socket of an extracted tooth in rats. Twenty male Wistar rats received cola beverage (cola group) or tap water (control group) ad libitum from the age of 23 days until tooth extraction at 42 days and euthanasia 2 and 3 weeks later. The neoformed bone volume inside the alveolar socket was estimated in semi-serial longitudinal sections using a quantitative differential point-counting method. Histological examination suggested a decrease in the osteogenic process within the tooth sockets of rats from both cola groups, which had thinner and sparser new bone trabeculae. Histometric data confirmed that alveolar bone healing was significantly delayed in cola-fed rats at three weeks after tooth extraction (ANOVA, p = 0.0006, followed by Tukey's test, p < 0.01). Although the results of studies in rats cannot be extrapolated directly to human clinical dentistry, the present study provides evidence that cola beverage consumption negatively affect maxillary bone formation.